2018
DOI: 10.1016/j.biochi.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new subtype of dipeptidyl peptidase 11 and a third group of the S46-family members specifically present in the genus Bacteroides

Abstract: Peptidase family S46 consists of two types of dipeptidyl-peptidases (DPPs), DPP7 and DPP11, which liberate dipeptides from the N-termini of polypeptides along with the penultimate hydrophobic and acidic residues, respectively. Their specificities are primarily defined by a single amino acid residue, Gly in DPP7 and Arg in DPP11 (numbering for Porphyromonas gingivalis DPP11). Bacterial species in the phyla Proteobacteria and Bacteroidetes generally possess one gene for each, while Bacteroides species exceptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Similar to the FADS (Met–Leu–ACA) sample, some species classified as Aeromonadaceae, Oxalobacteraceae, Weeksellaceae, or Pseudomonadaceae belong to the Proteobacteria or Bacteroidetes phylum and possess the S46 peptidases. 24 , 40 , 41 Therefore, these results support that the screening of microorganisms based on DPP activity using the dipeptidyl ACA substrates succeeded in enriching the abundance of microorganisms possibly through bacterial DPP7 or DPP11.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Similar to the FADS (Met–Leu–ACA) sample, some species classified as Aeromonadaceae, Oxalobacteraceae, Weeksellaceae, or Pseudomonadaceae belong to the Proteobacteria or Bacteroidetes phylum and possess the S46 peptidases. 24 , 40 , 41 Therefore, these results support that the screening of microorganisms based on DPP activity using the dipeptidyl ACA substrates succeeded in enriching the abundance of microorganisms possibly through bacterial DPP7 or DPP11.…”
Section: Resultssupporting
confidence: 61%
“…Some species classified as Xanthomonadaceae, Moraxellaceae, Oxalobacteraceae, or Weeksellaceae, which belong to Proteobacteria or Bacteroidetes, possess bacterial DPP7 and DPP11. 24 , 40 , 41 For the FADS (Leu–Asp–ACA) sample, the abundance ratio of Aeromonadaceae (denovo1771) increased the most, by 55.1-fold. The abundance ratios of Weeksellaceae (denovo1186), Oxalobacteraceae (denovo1645), and Pseudomonadaceae (denovo3742) increased 48.7-fold, 31.1-fold, and 23.3-fold, respectively, compared to the tofu factory waste fluid sample.…”
Section: Resultsmentioning
confidence: 99%
“…The acidic P1‐position residue is recognized by Arg673 in P. gingivalis DPP11. Biochemical studies have revealed that there are three subtypes of DPP11; (a) Porphyromonas‐ type DPP11, which is Asp‐preferential, (b) Bacteroides‐ type DPP11, which shows a high preference for Asp and scarcely accepts Glu, and (c) Shewanella‐ type DPP11, in which S1 Ser673 instead of Arg673, primarily exhibits higher preference for Glu (Nemoto et al., 2017).…”
Section: Degradation Of Extracellular Proteins Initiated By Gingipainsmentioning
confidence: 99%
“…Some bacterial genera e.g., Bacteroides [ 92 ] and Lactobacillus [ 93 ] secrete both peptidases and glycosidases and the more distal fiber-fermenting species Bacteroides thetaiotaomicron also express dipeptidylpeptidases (DPPs) [ 94 , 95 ]. Interestingly, the DPP4 antagonist vildagliptin, used for the treatment of T2D, induces a higher relative abundance of Bacteroidetes , a lower abundance of Firmicutes , and thus a reduced ratio of Firmicutes/Bacteroidetes in rats [ 96 ].…”
Section: The Plant Cell Wall Viewed As a “Pharmaceutical-nutrient mentioning
confidence: 99%